HEPATOPROTECTIVE EFFECT OF MANGIFERA-INDICA STEM BARK EXTRACTS ON PARACETAMOL-INDUCED OXIDATIVE STRESS IN ALBINO RATS - Omotayo, Mutiat Adetayo; Ogundare, Oyinlade Cecilia; Longe, Adeteju Oluwafunmilayo; Adenekan, Sunday (European Scientific Journal, ESJ, 2015)
This study was conducted to evaluate the hepatoprotective activity of aqueous and ethanol extract of Mangifera-indica stem bark in paracetamolinduced liver injury in winstar albino rats. Aqueous and ethanolic extracts of M. indica stem bark at a dose of 200mg/kg were administered for 7 days to rats in groups II and III respectively while vitamin C (200mg/kg) was given as a standard antioxidant to group IV along with water and standard feed. Groups I and V received water and standard feed for 7day. On the 8th day all groups except group I received paracetamol at a dose of 2g/kg body weight and all rats were sacrificed 12hrs after paracetamol administration. Serum total protein (TP), albumin, aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (ALP) were determined to assess the effect of the extract on the paracetamol induced hepatic damage in addition to hepatic antioxidant status. The ethanolic extract was found to be more effective than the aqueous extract (200 mg/kg) in paracetamol induced liver damage by decreasing the activity of serum enzymes AST, ALT and ALP while increasing significantly (P<0.05) the levels of total proteins and albumin. Glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) activity were significantly increased (P<0.05) in the treated groups while malondialdehyde (MDA) levels were reduced. From this studies it is concluded that both aqueous and ethanol extract of M. indica stem bark possesses hepatoprotective activity